Blended Learning to Remote Learning-The Role of Self-Directed Assessment - Ashley Edward Roy, Soosay (2022)
Online learning (OL) has become second nature in our current education arena. The unprecedented COVID-19 pandemic has expedited the evolution of OL. At the turn of the century Blended Learning (BL) emerged from the traditional electronic Learning. Today BL has evolved to Remote Learning (RL). Instructional Design is crucial for dissemination of knowledge not only in Face to Face Teaching and Learning mode but also in RL. The objective of this endeavour is to empower learners with meaningful RL experience. In order to achieve this a meticulously planned Online Instructional Design (OID) was used among learners of MDU1023 at Faculty of Medicine & Health Sciences, University Malaysia Sarawak (UNIMAS). Pertinent components of the learning process were highlighted and given preference in this OID for MDU1023. This OID consists of Micro Learning, Personalised Learning and Accessible Assessment. For the component of Accessible Assessment, Self-Directed Assessment (SDA) were made available for learners of MDU1023. SDA is a compilation of questions in a database with careful annotation and curation relevant to the learning outcome of the learning units of MDU1023. The access to SDA was via a Moodle platform known as electronic Learning Enrichment & Advancement Platform (eLEAP) at UNIMAS. Learners perception of the OID used in MDU1023 and in particular the SDA, were gauged via a google form questionnaire. Ninety-six percent response rate were obtained from a potential 77 learners. The learners reported that the educational techniques and eLEAP technologies used during the implementation of MDU1023 created a path for them to experience an impactful learning experience. Unanimous positive feedbacks were received on the implementation of this OID. Therefore, this is an evident that a well-planned Online Instructional Design facilitates and creates meaningful Remote Learning experience which is crucial for the current online education delivery system.